2021
DOI: 10.12688/hrbopenres.13204.1
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of psychological responses to COVID-19 in Irish healthcare workers: longitudinal quantitative and nested qualitative study

Abstract: COVID-19 is an unprecedent occurrence in modern times and individuals who work within healthcare settings, face a broad array of challenges in responding to this worldwide event. Key information on the psychosocial responses of such healthcare workers (HCWs) in the context of COVID-19 is limited and in particular there is a need for studies that utilise longitudinal methods, an overarching theoretical model, and use of a cohort of participants within a defined geographical area across acute and community setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
1
0
0
Order By: Relevance
“…The prevalence in the general population is estimated at around 3.9 to 22% [48,49], and among healthcare workers in general during the COVID-19 outbreak, the prevalence of insomnia reached 36% (Instrument: Insomnia Severity Index (ISS7)) [50], which shows that in the sample of EMS professionals analyzed, the presence of sleep problems was quite high compared to the general population and other healthcare workers. The most frequent psychological response in a group of Irish healthcare workers was difficulty initiating sleep [53]. A sleep study conducted in Bahrain on healthcare workers during the pandemic found that the sleep quality of the participants was poor, the number of hours for which they stayed asleep was reduced, and awakenings were frequent [54], consistent with the results found in the present study sample.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence in the general population is estimated at around 3.9 to 22% [48,49], and among healthcare workers in general during the COVID-19 outbreak, the prevalence of insomnia reached 36% (Instrument: Insomnia Severity Index (ISS7)) [50], which shows that in the sample of EMS professionals analyzed, the presence of sleep problems was quite high compared to the general population and other healthcare workers. The most frequent psychological response in a group of Irish healthcare workers was difficulty initiating sleep [53]. A sleep study conducted in Bahrain on healthcare workers during the pandemic found that the sleep quality of the participants was poor, the number of hours for which they stayed asleep was reduced, and awakenings were frequent [54], consistent with the results found in the present study sample.…”
Section: Discussionsupporting
confidence: 88%